The Impact of Bride Price Payment on Women’s Autonomy in Marital Relationship in Ankpa, Kogi State, Nigeria - Idris, Hussayn U.; Margaret, Tyagher (NIU Journal of Social Sciences, 2023)
The universally accepted concept of marriage is that between a man and a woman or women, and it is a social institution that cuts across different cultures both developing and the developed world, though, in practice variation exist from cultures to cultures. This variations for example, in a multicultural and multi religious society like Nigeria, could be a mix between traditional marriages, English marriage, court/registry or church marriages, and Islamic marriages, in some cases, it could be a hybrid of more than one of these types of marriages. In this situation a traditional wedding process starts and ends either in the courts, or the church or before an Imam. In Nigeria, presenting and accepting gifts is central to any marriage, a critical perusal of the role of the bride price in a marital relationship could help understand the role of female autonomy and possibly reduce some of the challenge’s women face in this social union.  Women’s autonomy is important for them to address matters aﬀecting their status as wives, their health and access to health facilities when they need to, and generally their fundamental human rights as human beings not just as housewives. The study examined married women’s perspectives on bride price and its impact on their autonomy in Ankpa. Employing phenomenological qualitative case study, A total of 20 in-depth interviews (IDI) and 10 focus group discussions (FGD)were conducted with married women in Ankpa. Rather than bride price, patriarchy, polygyny and gender role delineation, were responsible for the absence of female autonomy in marital relationships. Participants across all shades agreed that bride price was perceived as a necessary condition for validating marriages and according women respect as housewives and as a source of pride, rather than being responsible for the lack of female autonomy in the home. To address female autonomy among married women in Ankpa, patriarchy, polygyny and gender role delineation must be addressed. A woman’s capacity to address her reproductive health needs and access health care when in need must be understood as an inalienable right. Therefore, training, capacity building and education that will help build women’s capacity for independent decision-making is recommended. Keywords: Autonomy, Bride price, Culture, Gender, Multicultural, Patriarchy, Phenomenology, Patrilocal.